Race, work, and leadership : new perspectives on the black experience - Roberts, Laura Morgan; Mayo, Anthony J.; Thomas, David A., 1956- (Boston : Harvard Business Review Press, 2019)
Race, Work, and Leadership is a rare and important compilation of essays that examines how race matters in people's experience of work and leadership. What does it mean to be black in corporate America today? How are racial dynamics in organizations changing in a post-Obama era? How do we build inclusive organizations? Inspired by and developed in conjunction with the research and programming for Harvard Business School's 2018 celebration of the 50th anniversary of the founding of the HBS African American Student Union, this groundbreaking book shines new light on these and other timely questions and illuminates the present-day dynamics of race in the workplace. Contributions from top scholars, researchers, and practitioners in leadership, organizational behavior, psychology, sociology, and education test the relevance of long-held assumptions and reconsider the research approaches and interventions needed to understand and advance African Americans in work settings and leadership roles. At a time when there are fewer African American men and women in corporate leadership roles (following a peak in 2002), Race, Work, and Leadership will stimulate new scholarship and dialogue on the organizational and leadership challenges of African Americans and become the indispensable reference for anyone committed to understanding, studying, and acting on the challenges facing leaders who are building inclusive organizations.--
Foreword: Race in organizations: often cloaked but always present / by Ella L. J. Edmondson Bell and Stella M. Nkomo -- Why a volume on race, work, and leadership? / by Laura Morgan Roberts, Anthony J. Mayo, and Serenity Lee -- Section I. History and critical questions in black business leadership: A case study of leading change: the founders of Harvard Business School's African American student union / by Henry Louis Gates, Jr -- Pathways to leadership: black graduates of Harvard Business School / by Anthony J. Mayo and Laura Morgan Roberts -- Commentaries: The struggle is real: black colleges, resources, and respect / by Melissa E. Wooten -- Back to the future: a strategy for studying racism in organizations / by Arthur P. Brief -- Intersectionality and the careers of black women lawyers: results from the Harvard Law School Black Alumni Survey / by David B. Wilkins and Bryon Fong -- Section II. Comparative studies: Workplace engagement and the glass ceiling: the experience of black professionals / by Ella Washington, Ellyn Bass, & Shane McFeely -- Authenticity in the workplace: an African American perspective / by Patricia Faison Hewlin & Anna-Maria Broomes -- Feeling connected: the importance of engagement, authenticity, and relationships in the careers of diverse professionals / by Stacy Blake-Beard, Laura Morgan Roberts, Beverly Edgehill, & Ella Washington -- Section III. Phenomenological studies: the lived experience: Views from the other side: black professionals perceptions of diversity management / by Adia Harvey Wingfield -- Overcoming barriers to developing and retaining diverse talent in healthcare professions / by Laura Morgan Roberts, Stacy Blake-Beard, Stephanie Creary, Beverly Edgehill and Sakshi Ghai -- From c-suite to start-ups: an illusion of inclusion / by Toigo Foundation (Nancy Sims, Sue Toigo, Maura Allen & Toni Cornelius) -- Rough waters of resistance: black instructional coaches impacted by implicit bias / by Michelle Smith Macchia & Kish
Includes bibliographical references and index
Description based on print version record
Master record variable field(s) change: 050
Keywords: African American executives; African American leadership; Diversity in the workplace -- United States; Racism in the workplace -- United States; Corporate culture -- United States; African American executives; African American leadership; Corporate culture; Diversity in the workplace; Racism in the workplace; United States; elektronické knihy; electronic books